Development and characterization of microsatellite loci of Microglanis cottoides (Siluriformes: Pseudopimelodidae) and cross-species amplification - Souza-shibatta, Lenice; Ferreira, Dhiego Gomes; Oliveira, Claudio [UNESP]; Almeida, Fernanda Simões De; Shibatta, Oscar Akio; Sofia, Silvia Helena (Sociedade Brasileira de Ictiologia, 2013)
Thirteen microsatellite loci were isolated and characterized in Microglanis cottoides. Of these, two were monomorphic and 11 were polymorphic. These polymorphic loci tested on 24 individuals from a wild population produced a total of 108 different alleles, with levels of variability high, ranging from 2 to 20, with an average of 8.3 alleles per locus. The observed and expected heterozygosity ranged from 0.125 to 0.958 and from 0.119 to 0.931, respectively. A high combined probability of paternity exclusion value and a low probability combined genetic identity value obtained show that the set of loci described herein displays good suitability for paternity studies and differentiation of M. cottoides. Additionally, all thirteen microsatellite primers developed for M. cottoides were tested in four other Pseudopimelodidae species and successful cross-species amplification was achieved for the majority of loci.

Treze loci microssatélites foram isolados e caracterizados em Microglanis cottoides. Destes, dois foram monomórficos e 11 foram polimórficos. Estes loci polimórficos foram testados em 24 indivíduos de uma população selvagem e produziram um total de 108 alelos diferentes, com níveis de variabilidade alta, variando de 2 a 20, com uma média de 8,3 alelos por locus. A heterozigosidade observada e esperada variou de 0,125 a 0,958 e 0,119 a 0,931, respectivamente. Um elevado valor de exclusão de paternidade e um baixo valor de identidade genética foram obtidos, demostrando que o conjunto de loci descritos no presente trabalho exibe boa aplicabilidade no estudo de parentesco e diferenciação populacional em M. cottoides. Adicionalmente, os treze primers de microssatélites desenvolvidos para M. cottoides foram testados em outras quatro espécies de Pseudopimelodidae e a transferabilidade foi obtida para a maioria dos loci.
Keywords: Brazilian Eastern basin; Catfish; Enriched genomic library; Genetic marker; SSR